Cervical cancer mortality in brazilian regions: an overview from 2009 to 2019 (Research, Society and Development, 2023)
Cervical Cancer is the fourth disease that most kills women in Brazil and, therefore, the need to study and seek solutions. Purpose: to know mortality from cervical cancer in Brazilian women aged 20 to 80 years old, between the years 2009 to 2019. Methodology: this is a descriptive epidemiological study, to observe mortality from cervical cancer in women. Results: There were 62,386 deaths from cervical cancer during the period studied, with the highest mortality rate is in the North region and the lowest is in the Southeast region. The highest frequencies occurred in the age group between 50-59 years old with 13,964 deaths, and between 40-49 years old with 12,386 deaths. Conclusion: cervical cancer is a challenge to public health, with the need to strengthen disease prevention actions, health promotion and control of this type of cancer, in order to reduce its mortality and provide a quality of life for Brazilian women.